2008
DOI: 10.4049/jimmunol.180.11.7249
|View full text |Cite
|
Sign up to set email alerts
|

Human Tumor-Derived Exosomes Down-Modulate NKG2D Expression

Abstract: NKG2D is an activating receptor for NK, NKT, CD8+, and γδ+ T cells, whose aberrant loss in cancer is a key mechanism of immune evasion. Soluble NKG2D ligands and growth factors, such as TGFβ1 emanating from tumors, are mechanisms for down-regulating NKG2D expression. Cancers thereby impair the capacity of lymphocytes to recognize and destroy them. In this study, we show that exosomes derived from cancer cells express ligands for NKG2D and express TGFβ1, and we investigate the impact of such exosomes on CD8+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
419
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(430 citation statements)
references
References 43 publications
6
419
0
5
Order By: Relevance
“…In addition, NKG2D ligands may be secreted via exosomes maintaining their ability to modulate NKG2D cell surface levels [12]. Cancer-derived exosomes may downregulate receptor expression and reduce NK and CD8 + T cells functional responses, as reported recently [13,14]. Thus, the NKG2D recognition system has been postulated as a relevant mechanism in the immune response to cancer or in the tumor evasion from immunosurveillance [15,16].…”
Section: Introductionmentioning
confidence: 94%
“…In addition, NKG2D ligands may be secreted via exosomes maintaining their ability to modulate NKG2D cell surface levels [12]. Cancer-derived exosomes may downregulate receptor expression and reduce NK and CD8 + T cells functional responses, as reported recently [13,14]. Thus, the NKG2D recognition system has been postulated as a relevant mechanism in the immune response to cancer or in the tumor evasion from immunosurveillance [15,16].…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have shown the immunosuppressive properties of tumor-derived exosomes as well (Clayton et al, 2008;Raulet et al, 2013). The expression of NKG2D, FasL, and membrane-bound TGF-β, a representative immunosuppressive cytokine, in these exosomes appears responsible for the immunosuppression (Bianco et al, 2007;Borges et al, 2013;Fagiolo, 2004;Yoshimura and Muto, 2011).…”
Section: Physiological (Immunological) Roles Of Exosomesmentioning
confidence: 99%
“…In contrast, exosomes from immature DCs show a different protein profile including NFGE8 (a phagocytosis-inducing factor), FasL, and TRAIL (an apoptosis-inducing ligand) (Li et al, 2006). Recent data suggest that exosomes from tumor cells often express immunosuppressive ligands, such as NKG2D, whose expression allows the evasion of tumor cells from T cell and NK cell killing (Clayton et al, 2008).…”
Section: Molecular Composition Of Exosomesmentioning
confidence: 99%
“…Clinical researches showed reduced surface expression of NKG2D on circulating NK cells in cancer patients compared to healthy individuals. 40 Human prostate cancer cells-derived exosomes were found to express ligands for NKG2D, resulting in downregulation of NKG2D on NK cells and impaired NK cell cytotoxic function, 41 which might be due to TGF-b1 presented by TEX. 42,43 Neutralizing TGF-b1 antibody strongly abrogated NKG2D reduction on NK cells, suggesting TGF-b1 may be an effective mediator.…”
Section: Polarization Of Tumor-promoting Macrophagesmentioning
confidence: 99%